The Effect of Telerehabilitation to Improve Quality of Life in Patient of Heart Failure (HF) - Eza Kemal Firdaus; Diana Irawati; Melati Fajarini (Sekolah Tinggi Ilmu Kesehatan Kendal, 2023)
Heart failure is one of the biggest causes of death worldwide. The fragility of heart failure patients becomes more vulnerable and at greater risk of physical, functional, cognitive, and emotional decline leading to decreased quality of life. Telerehabilitation provides rehabilitation services at a distance through information technology and telecommunications, such as telephone, internet, and video conferencing conducted at the patient's home as an effective and safe complementary alternative in improving the quality of life. This study aimed to determine the quality of life before and after the implementation of Telerehabilitation. A quasi-experimental study of a single group. A purposive sampling technique was used to collect the data, with a sample of 17 respondents. Data was collected using a Minnesota Living with Heart Failure Questionnaire (MLHFQ) before and after the intervention. The statistical test used was Paired Sample T Test. Heart failure patients will carry out a telerehabilitation program that has been agreed upon by the nurse and doctor. The results of the Paired Sample T Test Quality of Life above show the P value (Sig. 2-tailed) 0.00 or less than 0.005 (<0.05), so it can be concluded that the implementation of Telerehabilitation affects improving the quality of life in Heart Failure patients.